Risk Perception of Cannabis Use Among a Sample of Thai Cannabis Users - Lamy, Francois R.; Paek, Seung Chun; Meemon, Natthani (Journal of Population and Social Studies [JPSS], 2024)
Amid the recent cannabis legalization in Thailand, this research captured and analyzed cannabis-related health risk perception among Thai cannabis users. This study used a cross-sectional design with 376 Thailand-based cannabis users recruited through an anonymous online survey from July to August 2022 using the SurveyMonkey application. Descriptive analysis and ordinary least squares regression analysis were performed to describe overall respondents’ characteristics and to identify predictors of low cannabis health-risk perception. Out of 376 respondents, 24.2% perceived cannabis as not risky for health, 46% considered cannabis as low risk, 26.6% as moderate risk, 2.7% as high risk, and 0.5% as most risky. Perceived risk of using cannabis was lower among respondents who had a higher perceived benefit of using cannabis (β = -0.133), a lower education level (β = -0.342), were full-time employed (β = -0.271,) and used cannabis more than twenty days in the past month compared to their counterparts (β = -0.373). Our results suggest that using cannabis in any form and frequency is perceived as a no to low health risk consumption by Thai cannabis users, calling for additional prevention and cannabis health literacy efforts.